Pengaruh Lingkungan Belajar Dan Motivasi Belajar Terhadap Prestasi Akademik Mahasiswasekolah Tinggi Ilmu Ekonomi Yapan Surabaya - Anastasia Anut; Tutik Winarsih (CV. Ulil Albab Corp, 2026)
This study examines how the academic achievement of students at STIE Yapan Surabaya is influenced by their learning environment and motivation. The relationship between variables was examined using quantitative methods with a causal associative study design. The Slovin algorithm with a 5% margin of error was used to calculate a sample size of 173 respondents. To ensure representative data collection, proportional random sampling was used as the sampling method. Multiple linear regression using IBM SPSS was used to analyze the data collected from the questionnaires that had undergone validity and reliability testing. The results showed that students' academic progress was positively and significantly influenced by the learning environment, indicating that performance improvement is encouraged in a more favorable and supportive environment. Academic success was also shown to be positively and significantly influenced by the desire to learn, indicating that individuals with greater drive typically succeed at a higher level. Academic achievement was positively and significantly influenced by the learning environment and learning motivation simultaneously. These results imply that increasing students' motivation levels and strengthening the quality of the learning environment are important tactics for improving overall academic outcomes.